(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This study examines the transformative impact of artificial intelligence (AI) and automation technologies on auditing practices. Through a systematic review of industry implementations and academic literature, we analyze how automated auditing enhances efficiency, accuracy, and risk detection while introducing new challenges related to data governance and ethical AI use. The findings demonstrate that automated auditing enables 100% population testing, reduces manual effort by 30-50%, and facilitates real-time compliance monitoring. However, successful implementation requires addressing data quality, model bias, and auditor upskilling